Gambaran Nilai Ankle Brachial Index (ABI) pada Pasien Diabetes Mellitus yang Mendapatkan Terapi BARKAH (Buerger Allen Exercise dengan Rendam Kaki Air Hangat): A Description of Ankle Brachial Index Values in Diabetes Mellitus Patients Receiving BARKAH Therapy (Buerger Allen Exercise with Warm Water Foot Immersion) - Della Juniana Sari; Suyanto; Mohammad Arifin Noor (Universitas Ngudi Waluyo, 2026)
Diabetes mellitus is a long-term metabolic condition that can impair peripheral blood flow, as reflected by reduced Ankle Brachial Index (ABI) measurements. BARKAH therapy, which combines Buerger Allen Exercise with warm water foot immersion, is a non-pharmacological approach intended to enhance peripheral circulation. This study aimed to describe ABI values among patients with diabetes mellitus following the application of BARKAH therapy. A quantitative descriptive design was employed in this study. ABI measurements were obtained using a Doppler instrument and analyzed through univariate techniques. The findings revealed that the majority of participants demonstrated ABI values within normal and acceptable ranges after undergoing BARKAH therapy. These results suggest that BARKAH therapy has the potential to contribute positively to the improvement of peripheral blood circulation in individuals with diabetes mellitus.